Biogeochemical drivers of interspecies electron transfer between iron reducers and methanogens - Hansen, Javil (Kansas State University, 2021)
Iron reduction and methanogenesis help drive the carbon cycle and in doing so influence greenhouse gas emissions and water quality. Microorganisms that drive the reactions can compete for energy sources or engage in syntropy via interspecies electron transfer (IET), but it remains unclear how environments influence which of these interactions occur. This study uses culturing experiments containing Geobacter metallireducens and Methanosarcina barkeri to better understand how interactions between an iron reducer and a methanogen, respectively, change with conditions. We examined interactions in iron reduction and methanogenesis in batch reactors with varying ferric iron mineralogy (none, ferrihydrite, lepidocrocite, goethite, and hematite) and acetate concentration (3 and 30 mM) and in semi-continuous cultures with varying acetate (3 and 30 mM) and bicarbonate (24 and 48 mM) concentrations but no ferric iron mineral. Results of the batch experiments show that amounts of methanogenesis varied considerably with ferric iron mineralogy and acetate supply. Average CH₄ generation was higher in cultures with 30 mM acetate than those with 3 mM acetate and decreased in order of hematite >> no ferric mineral ~ goethite > ferrihydrite > lepidocrocite. By comparison, the amount of iron reduction varied relatively little with acetate concentration and was lowest in cultures with hematite. In the semi-continuous cultures, CH₄ concentrations increased over time and reached the highest values in cultures with the 30 mM acetate and 24 mM bicarbonate. Carbon stable isotope compositions (δ¹³C) of CO₂ and CH₄ from both culturing experiments suggest that differences in CH₄ generation between cultures may in part reflect variation in the pathway of methanogenesis. Carbon isotopic compositions from cultures with hematite were consistent with CH₄ generation via acetoclastic methanogenesis. However, results from other cultures are more indicative of methanogenesis by CO₂ reduction. No hydrogen sources were available in the reactor to drive CO₂ reduction. Therefore, the result suggests that IET fueled much of the methanogenesis in the cultures. Taken together, our results indicate that the occurrence of IET can be influenced by ferric iron mineralogy and concentration of acetate. Impacts of IET on carbon isotope systematics in methanogenic systems require more attention. In particular, we need a better understanding of differences in the δ¹³C of CO₂ and CH₄ evolve as substrate consumption proceeds.
Keywords: Iron reducer; MethanogenInterspecies electron transfer